2023
DOI: 10.3390/ijms24032076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Normoxia- and Hypoxia-Modified Extracellular Vesicle Therapy in Function, Perfusion, and Collateralization in Chronically Ischemic Myocardium

Abstract: We have previously shown that normoxia serum-starved extracellular vesicle (EV) therapy improves myocardial function, perfusion, and angiogenesis in a swine model of chronic myocardial ischemia. Hypoxia-modified EVs have increased abundance of anti-oxidant, pro-angiogenic, and pro-survival proteins. The purpose of this study is to investigate the differential effects of normoxia serum-starved EVs and hypoxia-modified EVs on myocardial function, perfusion, and microvascular density in chronically ischemic myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…Two Yorkshire swine (male and female; Tufts University, Medford, MA, USA), aged 8 to 10 weeks and weighing between 22 and 25 kg at the time of the initial procedure, were used. This pilot study was designed to assess technical feasibility using an established model of chronic myocardial ischemia developed by Dr. Sellke as previously described [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. To induce chronic ischemia, a small left thoracotomy was performed, the pericardium was opened, and an ameroid constrictor composed of hygroscopic casein material cased in titanium (Research Instruments SW, Escondido, CA, USA) was sized and placed around the proximal left circumflex (LCX) coronary artery (Figure 2B).…”
Section: Animal Methodsmentioning
confidence: 99%
“…Two Yorkshire swine (male and female; Tufts University, Medford, MA, USA), aged 8 to 10 weeks and weighing between 22 and 25 kg at the time of the initial procedure, were used. This pilot study was designed to assess technical feasibility using an established model of chronic myocardial ischemia developed by Dr. Sellke as previously described [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. To induce chronic ischemia, a small left thoracotomy was performed, the pericardium was opened, and an ameroid constrictor composed of hygroscopic casein material cased in titanium (Research Instruments SW, Escondido, CA, USA) was sized and placed around the proximal left circumflex (LCX) coronary artery (Figure 2B).…”
Section: Animal Methodsmentioning
confidence: 99%
“…HBMSCs (Lonza) were cultured in accordance with the manufacturer's recommendations using growth medium (MSCGM Bulletkit PT-3001; Lonza), as described previously. 13 HYP EVs were grown until they reached 80% confluence and then passaged to passage 7. At this stage, the medium was replaced with MSCGM medium, and the cells were placed in a humidified hypoxia chamber (MIC-101; Billups-Rothenberg) containing 5% carbon dioxide and 95% nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…At this stage, the medium was replaced with MSCGM medium, and the cells were placed in a humidified hypoxia chamber (MIC-101; Billups-Rothenberg) containing 5% carbon dioxide and 95% nitrogen. 13 The cells were incubated at 37 °C for 24 hours, after which the medium and the EVs were collected via ultracentrifugation as described previously. 13 Protein quantification was performed using a radioimmunoprecipitation assay (Kit 23225; Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, two studies that investigated the impact of EVs derived from human bone mesenchymal stem cells on angiogenesis demonstrated that the application of these EVs to ischemic heart tissue resulted in improved angiogenic signaling via the Akt and ERK pathways. Moreover, these EV-treated tissues exhibited decreased levels of anti-angiogenic markers, suggesting their potential suitability for treating conditions characterized by a reduced blood flow or capillary density, such as heart failure or myocardial ischemia [ 87 , 88 , 89 ]. Another paper on glioblastoma demonstrated how vesicles play a crucial role in information exchange between malignant and vascular cells, the release of growth factors and cytokines by endothelial cells, activation of the PI3K.AKT signaling pathway, and the movement of pericytes.…”
Section: Role Of Evs In Angiogenesismentioning
confidence: 99%